Analysis of the Effect of Economic Education on Students' Entrepreneurial Attitudes in the Era of Digital Transformation - Novie Kurniasih Kamarudin; Jamil Latief; Naufal Ramadian; Muhamad Alimudin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The rapid advancement of digital technology has significantly transformed economic activities and entrepreneurial practices, creating both opportunities and challenges for university graduates. In response to these changes, higher education institutions are expected to foster entrepreneurial attitudes that align with the demands of the digital economy. This study aims to examine the effect of economic education on students’ entrepreneurial attitudes in the era of digital transformation. A quantitative research design was applied using a survey method involving undergraduate students who had completed economic education courses. Data were collected through structured questionnaires that measured learning outcomes in economic education and entrepreneurial attitudes, including creativity, innovation, risk-taking, opportunity recognition, and adaptability to digital technologies. The data were analyzed using descriptive statistics and multiple regression analysis to assess the relationship between economic education and entrepreneurial attitudes. The findings show that economic education has a positive and significant effect on students’ entrepreneurial attitudes. Students with higher levels of economic understanding tend to demonstrate stronger entrepreneurial characteristics that support innovation and adaptability in digitally driven business environments. These results indicate that economic education is important not only for strengthening students’ economic knowledge but also for developing the entrepreneurial mindset needed to respond to the challenges of the digital era. The study also reinforces the link between economic education and entrepreneurship in the setting of digital transformation. In practical terms, the findings may serve as a reference for educators and policymakers in designing economic education programs that are more oriented toward entrepreneurship in higher education.